Parental Support and Underrepresented Students' Math/Science Interests: The Mediating Role of Learning Experiences. (November 2014) - Garriott, Patton O.; Flores, Lisa Y.; Prabhakar, Brinda; Mazzotta, Elizabeth C.; Liskov, Alana C.; Shapiro, Jaclyn E.
Using social cognitive career theory (SCCT), the present study examined the role of parental support and investigative learning experiences (i.e., performance accomplishments, verbal persuasion, vicarious influence, physiological arousal) in the development of math/science interests among high school students of color ( N = 206). Results of structural equation modeling analyses suggested the hypothesized model adequately fit the data. Parental support significantly predicted each learning experience variable, with the exception of physiological arousal. Performance accomplishments were the only learning experience variable that predicted both math/science self-efficacy and math/science outcome expectations. Self-efficacy significantly predicted interests, but did not predict outcome expectations. Furthermore, outcome expectations did not predict interests. Mediation tests indicated that performance accomplishments, vicarious learning, and self-efficacy mediated relationships between contextual and person-cognitive variables. Results are discussed in relation to SCCT and the development of career interests in math/science among underrepresented students.